2008
DOI: 10.1097/qai.0b013e31818c953f
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Analogues Show Suitable Stability for Development as Microbicides

Abstract: New prevention strategies are urgently needed to slow the spread of the HIV/AIDS pandemic, and in the absence of an effective vaccine, there is hope that "microbicides"-HIV inhibitors applied to mucosal surfaces before sexual intercourse-may be able to make an impact. Because developing countries are at the center of the epidemic, affordability and stability during storage are key criteria for candidate microbicides. Furthermore, because formulation strategies that provide long-duration protection after a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…However, because of its strong CCR5 agonist activity that might induce local inflammation and because of the high production costs, the development of PSC-RANTES as a microbicide was stopped and efforts were put in finding recombinant analogues that retained the high potency and lacked the cellular activation associated with PSC-RANTES. Of these, 5P12-RANTES has the most interesting profile [186,187]; it combines very potent activity against a broad range of HIV subtypes, lacks signalling activity, does not induce CCR5 receptor sequestration and can be produced at low cost. More recent studies in Rhesus macaques showed complete protection by 5P12-RANTES against vaginal challenge with a SHIV [188].…”
Section: Entry/fusion Inhibitorsmentioning
confidence: 99%
“…However, because of its strong CCR5 agonist activity that might induce local inflammation and because of the high production costs, the development of PSC-RANTES as a microbicide was stopped and efforts were put in finding recombinant analogues that retained the high potency and lacked the cellular activation associated with PSC-RANTES. Of these, 5P12-RANTES has the most interesting profile [186,187]; it combines very potent activity against a broad range of HIV subtypes, lacks signalling activity, does not induce CCR5 receptor sequestration and can be produced at low cost. More recent studies in Rhesus macaques showed complete protection by 5P12-RANTES against vaginal challenge with a SHIV [188].…”
Section: Entry/fusion Inhibitorsmentioning
confidence: 99%
“…In a complementary effort, antibodies (7, 148) and therapeutic nucleotides (35, 53, 95) are pursued as agents targeting chemokines. With all of these agents, oral availability is out of question; however, various approaches to improving metabolic stability have been successful (18, 95). In combination with the ample potential for optimization of receptor inhibition properties, this suggests that biologics and biomimetics may become a promising next generation class of therapeutics targeting the chemokine receptor system.…”
Section: On Druggability Of Chemokine Receptorsmentioning
confidence: 99%
“…Griffithsin (Grft) is a lectin derived from red alga 16 that binds the HIV envelope glycoprotein gp120 and is among the most potent lectin inhibitor of HIV as well as exhibiting effectiveness against other enveloped viruses including SARS and Hepatitis C 17,18 . Both 5P12-RANTES and Grft have been shown to have properties suitable for microbicidal use, including stability over a wide pH range and inexpensive production in large quantities [19][20][21][22] . Furthermore, chimeras formed by fusing 5P12-RANTES or Grft with the HIV gp41-derived C-peptide C37 via a covalent linkage, namely 5P12-RANTES-L-C37 and Grft-L-C37, have consistently shown even higher potency and wider breadth of inhibition than the original proteins 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…These proteins were selected based on a combination of properties, including high potency to broadly neutralize many strains of HIV, and experimentally determined suitability as HIV microbicides 19,22 . SF disks are expected to be amenable to users, with easy insertion, followed by release of inhibitor in response to the body's own moisture.…”
Section: Introductionmentioning
confidence: 99%